Proteomics as a tool to improve novel insights into skin diseases: what we know and where we should be going - Zheng, Sheng-yuan; Hu, Xi-min; Huang, Kun; Li, Zi-han; Chen, Qing-ning; Yang, Rong-hua; Xiong, Kun (Frontiers in Surgery, 2022)
Background: Biochemical processes involved in complex skin diseases (skin cancers, psoriasis, and wound, etc.) can be identified by combining proteomics analysis and bioinformatics tools, which gain a next level insight into their pathogenesis, diagnosis and therapeutic targets. Methods: The articles were identified through a search of PubMed, Embase, and MEDLINE references date to May 2022, using to perform a system data mining. And a search of the Web of Science (WoS) Core Collection was utilized to conduct visual bibliometric analysis Results: An increased trend line revealed that the number of publications related to proteomics utilized in skin diseases has sharply increased recent years, reaching a peak in 2021. The hottest fields focused on the skin cancer (melanoma), inflammation skin disorder (psoriasis) and skin wounds. After deduplication, title, abstract and full-text screening, a total of 486 of the 7,822 outcomes met the inclusion/exclusion criteria for detail data mining in the field of skin disease tooling with proteomics, when it comes to skin cancer. According to the data, cell death, metabolism, skeleton, immune and inflammation enrichment pathways are likely the major part and hotspots of proteomic analysis found in the skin diseases. Also, the focuses of proteomics in skin disease are from superficial presumption to depth mechanism exploration within more comprehensive validation, from basic study to a combination or guideline for clinical application. Further, we took skin cancer as a typical example, also compared with other skin disorders. Besides utilized in variation analysis in different diseases or compared with healthy group, proteomic analysis has been used in evaluation of treatment, or may further in generality, specificity, and others to gain a depth mechanism and guideline in the field of skin diseases. Conclusion: Proteomics has been regarded as an irreplaceable technology in the study of pathophysiological mechanism or/and therapeutic targets of skin diseases, which could provide with candidate key proteins for the insight into the biological information after gene transcription. However, depth pathogenesis and potential clinical applications need further studies with more stronger evidences within a wider range of skin diseases.